THE CHANGE OF GOVERNMENTAL IMPLICATION ON PUBLIC POLICY MAKING: LESOTHO’S E-GOVERNMENT EXPERIENCE - Molefi Matsieli; Radhamany Sooryamoorthy (Universitas Nasional, 2023)
In Lesotho in recent years, government changeover has become a topic of interest among the electorate, journalists, foreign missions, civil organisations and beyond. Similarly, election commentators, political analysts and researchers alike have discussed 'who climbs to power' and 'how do they ascend to' or 'descend from power'. Significantly less efforts have been focused on the effects of a new administration. This paper attempts to contribute to the existing body of knowledge by examining the relationship between a change of government and the priorities in policy. This is achieved by examining the implications for change of the executive power on the policy making in Lesotho. Using the e-government experience of Lesotho based on the changeovers of 2012, 2015 and 2017, it was found that the executive turnover has a direct, yet antagonistic effect on policies. The results show that often a new administration either goes slowly with or discontinues the policies, programmes and projects of the predecessor. This not only widens the policy-implementation gap as service delivery is interrupted, consequently leading to a lapse in solving problems in the society. It also creates uncertainty, not necessarily about who comes to power, but about what policy direction they will pursue.